Analysis of Indonesia Mineral and Coal Mining Safety Management System Policy Using Soft System Methodology - Anggoro, Yudo; Simorangkir, Dean Andreas (SBM ITB, 2019)
Abstract. After 3 years the Ministry of Energy and Mineral Resources Regulation (MEMR) No. 38 of 2014 on Mineral and Coal Mining Safety Management System was published, Mining Companies in Indonesia are still having difficulties in applying this regulation. In this study, the gap between the current and the expected condition are quantified, the causes are described, and strategies to improve the situation are developed by using Soft System Methodology. The population of this study is limited to mining companies whose permits are granted by MEMR. The results of evaluation showed that only 41% had achieved the expected level, as for now there are many barriers including: 1) Internal Factor: lack of understanding, management support and unstable workforce; 2) Difficulties in managing service companies); 3) Nature of Company: lack of resources, lack of familiarity with system concept); 4) Poor Audit; and 5) Lack of information from Government. This policy should be continued. The Government Interventions should be taken, including: 1) Promotion to Top Level Management; 2) Competency Development for Mine Inspector and Mining Companies; 3) Setting Minimum Criteria for Service Companies; 4) Optimizing the Audit; 6) Supervision; 7) Safety Award; 7) Strict Sanctions; 8) Increasing Awareness and Recognition.Keywords: Mining, occupational health and safety management, public policy evaluation, soft system methodology, system thinkingAbstrak. Setelah tiga tahun Peraturan Menteri Energi dan Sumber Daya Mineral Nomor 38 Tahun 2014 tentang Penerapan Sistem Manajemen Keselamatan Pertambangan Mineral dan Batubara, Perusahaan Pertambangan masih mengalami kesulitan dalam menerapkannya. Dalam studi ini, kesenjangan antara kondisi saat ini dan yang diharapkan diukur, penyebab kesenjangan dijelaskan, dan strategi untuk memperbaiki situasi dikembangkan dengan Soft System Methodology. Penelitian ini terbatas pada perusahaan pertambangan yang izinnya diterbitkan oleh Kementerian ESDM. Hasil evaluasi menunjukkan bahwa hanya 41% perusahaan yang telah mencapai tingkat penerapan yang diharapkan, dimana terdapat banyak kendala implementasi, antara lain: 1) Faktor Internal Perusahaan: kurangnya pemahaman, dukungan manajemen, dan tidak tetapnya tenaga kerja; 2) Kesulitan dalam mengelola perusahaan jasa penambangan); 3) Sifat Perusahaan: kurangnya sumber daya, kurang terbiasa dengan konsep sistem; 4) Tidak optimalnya pelaksanaan audit: dan 5) Kurangnya informasi dari program pemerintah. Secara umum, kebijakan ini memiliki tujuan baik dan harus dilanjutkan. Intervensi Pemerintah yang harus diambil untuk memperbaiki situasi, antara lain: 1) Sosialisasi kepada Manajemen Tingkat Puncak Perusahaan; 2) Pengembangan Kompetensi untuk Inspektur Tambang dan Perusahaan; 3) Penetapan Kriteria Minimal Implementasi untuk Perusahaan Jasa; 5) Optimalisasi Fungsi Audit; 6) Pengawasan; 7) Inovasi untuk Safety Award; 8) Pemberian Sanksi Tegas; 9) Peningkatan Kesadaran dan Pengakuan.Kata kunci: Evaluasi kebijakan publik, keselamatan dan kesehatan kerja, pertambangan, soft system methodology, system thinking